Non-specific red cell reactivity in an obstetric population. (1st September 2016) - Van Winden, Kristi R.; Poisson, Jessica L.; Lee, Richard H.; Agarwal, Ravi; Ouzounian, Joseph G.; Shulman, Ira A.
Abstract: Objective : To examine non-specific red cell reactivity (NSR) on antibody (Ab) screening of obstetric inpatients. Methods : Observational study of 5438 obstetric inpatients (2009–2013). Ab-positive patients were identified and their records reviewed for NSR, other antibodies, transfusion reactions or hemolytic disease of the fetus/newborn (HDFN). Evaluation of NSR frequency by test era assessed the impact of an institutional change to solid-phase screening in 2011. Results : Of obstetric inpatients, 5.3% had at least one positive Ab screen; 1.6% had NSR. Of NSR-positive patients, 16.7% had identifiable Abs that pre-dated NSR; 25% had concurrent Abs and 8.5% had subsequent Ab identification. In 49.1%, NSR resolved during follow-up. The frequency of NSR was higher after the change to solid-phase Ab screening, but specific Ab frequency was similar in both testing periods. No transfusion reactions or cases of HDFN were noted in this cohort. Conclusions : NSR is found in 1–2% of obstetrical inpatients at our institution, and has more than doubled since the initiation of solid-phase screening. Although likely clinically insignificant by itself, NSR is commonly found in relation to other red cell Abs and may precede their development.